Edukasi “Isi Piringku” pada Remaja dalam Upaya Cegah Stunting di SMA Islam Al Falah Kota Jambi - Hatussaadah, Siti Fati; Chandra, Filius (Universitas Baiturrahim, 2025)
Stunting during adolescence will affect psychomotor development, fine motor skills and neurosensory integration, the level of intelligence and the lack of competitiveness that children have in the fields of development and the economy. Nutrition in adolescents determines the optimization of learning, maturation of thought patterns and optimization of the work of organ systems. A teenager's diet will determine the amount of nutrients they obtain for their growth and development.